Innovative Strategies for Optimizing New Student Admissions in Madrasah Aliyah - Rahma, Rahma; Yuniar, Yuniar; Mardeli, Mardeli; Annur, Saipul (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to analyze and discusses strategies and innovations in the New Student Admissions (PPDB) System at MAN IC OKI. This type of research is field research with a qualitative approach. Data collection methods use observation, interviews, and documentation. Observation to observe the implementation process, interviews by asking questions related to policies, rules, and implementation, while documentation is to analyze various documents such as requirements and brochures. Data analysis methods use data reduction, data presentation, and drawing conclusions. Research findings indicate that the strategies and innovations implemented successfully enhance the efficiency of the selection process and the quality of students admitted. Evaluation of these strategies shows a significant increase in the number of applicants and students admitted annually, as well as an improved public trust in the transparency and objectivity of the student admission system at the madrasah. Overall, MAN IC OKI has modernized the PPDB system through holistic and innovative strategies, ensuring that admitted students not only possess high academic quality but are also prepared to face challenges in the modern world. By continuing to develop these strategies, the school can further contribute to enhancing education in Indonesia through admitting highly competitive and character-driven students. The efficient and transparent admission of new students is crucial for maintaining the educational standards and reputation of institutions.